Peran Kegiatan Muhadoroh dalam Meningkatkan Kepercayaan Diri dan Interaksi Sosial Peserta Didik SMPIT Al Bina Purwakarta - Widia Alawiyah; Septi Gumiandari (STIKes Ibnu Sina Ajibarang, 2026)
The muhadoroh activity in schools should serve to enhance students' self-confidence and social interaction skills. However, many students still experience anxiety and difficulty in communicating effectively in public. This indicates that muhadoroh activities have not yet fully optimized their role in supporting students' personal and social development. This study aims to explore students' experiences in participating in muhadoroh, describe its contribution to increasing self-confidence, analyze its role in developing social interaction, and identify the correlation between both. The study uses a qualitative approach with a descriptive design, collecting data through interviews and observations of eight informants, including students, OSIS administrators, OSIS advisors, and the principal at SMPIT Al Bina Purwakarta. The findings show that: (1) nervousness decreases through habituation and repeated practice, (2) muhadoroh activities contribute significantly to enhancing students' self-confidence, (3) it strengthens social interactions through collaboration and discussion, and (4) there is a positive relationship between self-confidence and the quality of social interactions. This research enriches the study of experiential learning in Islamic education and is expected to serve as a reference for optimizing muhadoroh activities in schools.